STRATEGI PENANGANAN PEMBIAYAAN YANG BERMASALAH TERHADAP PT. BANK SUMUT SYARIAH CABANG MEDAN KATAMSO) - Azzahra, Maylin; Dalimunthe, Ahmad Amin (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The current research is focused on what are the triggers that lead to problematic financing as well as solutions from banks to these customer problems at PT. Bank Sumut Syariah Medan Katamso Branch Office. The method used is descriptive qualitative. Where the researchers carried out this method by collecting information through question and answer sessions from resource persons, research and also data studies. Researchers found lots of lists of problematic financing customers at PT. Bank Sumut Syariah Medan Katamso Branch. This problematic financing itself means a situation where the debtor cannot or is able to meet his needs for Islamic financial institutions or in short, it can be said that the customer is unable to pay installments to the bank. The results obtained are the main cause of this problematic financing, namely because the customer is no longer able to fulfill his responsibilities to the bank, besides that it is also the character of the customer who is of course deliberately not paying the arrears that occur. So the steps taken by the bank if the customer still has good faith are reschedule, restructuring, reconditioning. However, if there is nothing more to be expected from the customer, then what is done is confiscation, emptying, and then auctioning. This is the last key done by the bank so as not to suffer losses.